Wound healing property of Basil gel formulated from ocimum basilicum linne (Family lamiacea) - Bulatao, Bryan Paul I.
Ocimum basilicum Linne (Family Lamiaceae), commonly known as basil, is known to have antimicrobial and anti-inflammatory properties. The objective of this study was to investigate the wound healing activity of basil as formulated into a gel. Fresh basil leaves were percolated using ethanol as a solvent for 24 hours. Phytochemical analysis performed on the extract revealed the presence of alkaloids. Preformulation and formulation studies of the extract were conducted to ascertain its feasibility for a large-scale production. Sodium carboxymethylcellulose (CMC), methyl paraben, propyl paraben and propylene glycol were used in the final formulation. The formulated Basil Gel was translucent, light green in color with a strong, spicy smell and had a pH of 5.7. Basil Gel did not cause any dermal irritation, such as erythema and eschar, and edema upon application on albino rabbits. The wound healing property of Basil Gel was assessed using 15 albino mice each under the incision and excision wound models. Incision and excision wounds were evaluated by wound-breaking strength and wound contraction measurements, respectively. Histopathological study was also performed on both types of wound. Statistical studies using One-Way Analysis of Variance (ANOVA), paired t-test and Friedman test were also conducted. Results of the tests revealed that Basil Gel is as effective as Solcoseryl Jelly as a wound healing agent. Basil Gel is estimated to be cheaper than the wound healing products available in the market.